Pengaruh Pelatihan Kerja, Kompensasi Finansial Dan Pengembangan Karir Terhadap Kinerja Karyawan (Studi PT. Prakarsa Pramandita Seram Bagian Timur, Maluku) - Ali, Risa Risanti; Djaelani, Abdul Kodir; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2023)
Abstract His research aims to determine the influence of job training, financial compensation and career development on employee performance PT. Prakarsa Pramandita Seram Bagian Timur, Maluku. In this research, three independent variables were used, namely job training, financial compensation and career development and one dependent variant, namely employee performance. This research uses a quantitative type of research. The research data collected is through a questionnaire using a likert scale and the data analysis used was multiple linear regression which was tested using SPSS version 24. Taking sample data using the Slovin formula with an error scale of 0.5, namely obtaining 32 respondents. The results obtained showed that job training had a positive effect on employee performance PT. Prakarsa Pramandita Seram Bagian Timur, Maluku. Financial compensation has a positive effect on employee performance PT. Prakarsa Pramandita Seram Bagian Timur, Maluku. Career development has a positive effect on employee performance PT. Prakarsa Pramandita Seram Bagian Timur, Maluku. There is a simultaneous influence between job training, Financial Compensation and Career Development variables on employee performance PT. Prakarsa Pramandita Seram Bagian Timur, Maluku. Based on the research results, researchers can provide advice to interested parties to obtain benefits, namely for the company to maintain performance so that the company can maintain the quality designed by the company's leadership. Other research can be developed by adding other variables and it is recommended to add a wider number of respondents. Keywords: Job Training, Financial Compensation, Career Development, Employee Performance